Triterpenoids from Aglaia shawiana with their Cytotoxicity against MDA-MB468 and MCF-7 Cancer Cell Lines - Ricson Pemimpin Hutagaol; Tjandrawati Mozef; Gian Primahana; Sofa Fajriah; Nuralih Nuralih; Fitri Nur Aini; Desy Setyaningsih (Universitas Jenderal Soedirman, 2026)
Triterpenoids are secondary metabolite compounds that are predominantly found in plants of the genus Aglaia. Since the 1960s, various triterpenoid structures from Aglaia species have been successfully isolated, and many are known to have interesting biological activities. This study aims to find triterpenoid compounds from Aglaia shawiana, which will then be tested for their activity against two breast cancer cell lines, MCF-7 and MDA MB 468. This research is expected to be used as a basis for further study in the development of cancer drug substances from Aglaia triterpenoids. Two triterpenoids were isolated from n-hexane extract of Aglaia shawiana leaves and twigs which is, namely cycloartan-3β,29-diol-24-ones (1), and 3-epi-cabraleahydroxylactone (2). Their chemical structures were determined based on spectroscopic data using infrared, high-resolution mass spectrometry, and including one and two-dimensional NMR techniques. Comparative data analysis was also carried out with appropriate reference journals and through a biosynthesis approach of the triterpene compounds. Both compounds were evaluated for their cytotoxic effects on MCF-7 and MDA MB-468 breast cancer cells. Compound 1 showed cytotoxicity with IC50 values of 118,2668 and 3,6505 µg/ml, meanwhile compound 2 values of 115,1065 μg/ml and 14,5274µg/ml, respectively. Doxorubicin used as a positive control with IC50 values of 3,2724 and 0,0303 µg/ml, respectively.